ANALISIS KADAR VITAMIN C PADA BAWANG MERAH (Allium cepa L.) JENIS BATU, SUMENEP, DAN TUTUG DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Dadang Muhammad Hasyim (Jurnal Sains dan Teknologi Laboratorium Medik, 2022)
Shallot (Allium cepa L.) is a vegetable spice that is widely used as a food seasoning to add flavor and enjoyment to cooking. Shallots are also widely used as a powerful traditional medicinal ingredient to treat various health problems. Shallots contain various kinds of nutrients and vitamins. One of the vitamins contained in shallots is vitamin C which acts as an antioxidant and is effective in dealing with free radicals that damage cells or tissues. This study aims to determine the levels of vitamin C in several types of shallots. The types of shallots in this study were stone shallots, sumenep shallots, and tutug shallots. Analysis of vitamin C levels was carried out using the UV-Vis spectrophotometry method at a wavelength of 515 nm. Results of the analysis showed that the vitamin C levels of stone shallots were 1.043 mg/100 g, Sumenep shallots were 1.638 mg/100 g, and tutug shallots were 1.296 mg/100 g. Vitamin C levels in Sumenep shallots have the highest levels compared to those of stone shallots and tutug shallots.